1990
DOI: 10.1007/bf01387183
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization of water soluble, allergenic proteins in rye-grass (Lolium perenne) pollen using monoclonal and specific IgE antibodies with immunogold probes

Abstract: A postembedding method has been developed for localizing water soluble allergens in rye-grass pollen. This uses dry fixation in glutaraldehyde vapour, followed by 2,2-dimethoxypropane, prior to a 100% ethanol series leading into embedment in LR Gold. This has allowed the attachment of specific monoclonal antibodies to the allergen, which are themselves probed with specific immunogold labels to the antibodies. Wall and cytoplasmic sites have been identified, representing an improvement of fixation and localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 41 publications
1
37
0
1
Order By: Relevance
“…Belin & Rowley (1971) concluded that the allergens in Behrln are probably stored inside the pollen protoplasm and diffuse through the aperture during germination. Staff et al (1990), Taylor et al (1994) and Knox & Suphioglu (1996) localized allergens in the starch grains and cytosol of rye-grass pollen. Our aim with the present study is to determine the localization of the allergens in the cytoplasmic organelles and pollen wall of Berulupnidirln, using monoclonal antibody and immunocytochemistry.…”
mentioning
confidence: 99%
“…Belin & Rowley (1971) concluded that the allergens in Behrln are probably stored inside the pollen protoplasm and diffuse through the aperture during germination. Staff et al (1990), Taylor et al (1994) and Knox & Suphioglu (1996) localized allergens in the starch grains and cytosol of rye-grass pollen. Our aim with the present study is to determine the localization of the allergens in the cytoplasmic organelles and pollen wall of Berulupnidirln, using monoclonal antibody and immunocytochemistry.…”
mentioning
confidence: 99%
“…The MAbs 1D8 and l6G2 also recognized proteins in these areas in all species tested here (Figures 4-6). This nuclear labeling, likewise observed in rye grass pollen (Staff et al, 1990) and birch pollen (Grote 1991), may reflect the nonspecific attraction of the gold probe to nuclear material (Staff et al, 1990). Alternatively, nuclear labeling may be considered evidence of free dlffusion of the small allergen molecule into the nucleus via the nuclear pores, as suggested by Grote (1991).…”
Section: Discussionmentioning
confidence: 79%
“…Earlier studies with light microscopy (LM) and transmission electron microscopy (TEM) have reported the localization of allergens in pollen from ragweed, ryegrass, mugwort, birch, alder, Japanese cedar, and hazel, among other allergenic species (Avjioglu et al, 1994;Grote et al, 1994;Miki-Hirosige et al, 1994;Kos et al, 1993;Vrtala et al, 1993;Singh et al, 1991;Staff et al, 1990).…”
Section: (J Hisrochem Cytochem 46951-158 19%)mentioning
confidence: 99%
“…Other clinically relevant allergens are those of groups 2, 3, 4 and 13, which are recognized by over 50% of grass pollen allergic individuals 22 . Lol p 1 and Lol p 5, the main cloned and sequenced groups 1 and 5 L. perenne allergens [23][24][25] , are located in different compartments: Lol p 1 is found in the cytosol 26,27 and Lol p 5 is associated with grass pollen starch grains 25 . Additionally, the occurrence of many antigen components with a similar molecular mass within a same species may be due to isoforms, such as those seen in Lol p 1 and Lol p 5 (isoforms 4 and 8, respectively) 28 .…”
Section: Grass Species Producing Allergenic Pollenmentioning
confidence: 99%